Electromechanical product refabrication device - WEI HONGSHENG (2018)
The invention discloses an electromechanical product refabrication device. The electromechanical product refabrication device comprises an installation seat, four corners of the bottom surface of theinstallation seat are fixedly provided with support legs, the bottom surface of each support leg is fixedly provided with a sucking disc used for being adsorbed to the ground, the left side of the upper end surface of the installation seat is fixedly connected with an installation block, the right side of the upper end surface of the installation seat is provided with a second sliding block, the center point of the upper end surface of the installation seat is provided with a horizontal first sliding groove, the left end of one rotating connection shaft penetrates through one rotating connection hole and is detachably and fixedly connected with a first polishing wheel, the left end of one other rotating connection shaft penetrates through one other rotating connection hole and is fixedly connected with a fixator,